Management of children and adolescents with chronic myeloid leukemia in blast phase: International pediatric CML expert panel recommendations - Sembill, Stephanie; Ampatzidou, Maria; Chaudhury, Sonali; Dworzak, Michael; Kalwak, Krzysztof; Karow, Axel; Kiani, Alexander; Krumbholz, Manuela; Luesink, Maaike; Naumann-Bartsch, Nora; De Moerloose, Barbara; Osborn, Michael; et al. (Leukemia, 2023)
Treatment of chronic myeloid leukemia has improved significantly with the introduction of tyrosine kinase inhibitors (TKIs), and treatment guidelines based on numerous clinical trials are available for chronic phase disease. However for CML in the blast phase (CML-BP), prognosis remains poor and treatment options are much more limited. The spectrum of treatment strategies for children and adolescents with CML-BP has largely evolved empirically and includes treatment principles derived from adult CML-BP and pediatric acute leukemia. Given this heterogeneity of treatment approaches, we formed an international panel of pediatric CML experts to develop recommendations for consistent therapy in children and adolescents with this high-risk disease based on the current literature and national standards. Recommendations include detailed information on initial diagnosis and treatment monitoring, differentiation from Philadelphia-positive acute leukemia, subtype-specific selection of induction therapy, and combination with tyrosine kinase inhibitors. Given that allogeneic hematopoietic stem cell transplantation currently remains the primary curative intervention for CML-BP, we also provide recommendations for the timing of transplantation, donor and graft selection, selection of a conditioning regimen and prophylaxis for graft-versus-host disease, post-transplant TKI therapy, and management of molecular relapse. Management according to the treatment recommendations presented here is intended to provide the basis for the design of future prospective clinical trials to improve outcomes for this challenging disease.
Keywords: Leukemia, Myeloid, Acute; transplantace hematopoetických kmenových buněk; Humans; dítě; Graft vs Host Disease; Hematopoietic Stem Cell Transplantation; Child; dospělí; lidé; Adult; Blast Crisis; chronická myeloidní leukemie; nemoc štěpu proti hostiteli; Adolescent; prognóza; blastická krize; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; akutní myeloidní leukemie; Prognosis; mladiství